(3GdefGgL GdShjI TQM GdQhVI GdHgjIs - (3GdCUagGfj, GdaGVd GdgfOj (B, (3HgGA GdOjf, eMeO Hf MSf Hf eMeO, J (B1137 (3g`s ((3eMeO Ydj Hf eMeO bGSe GdbheTgQs)
(3ChdgG (B:s
(3HSe Gddg (B.. (3cJGH GdUdGI ; bjd gj ef GdUdGI HeYfi GdOYGA dGTJeGdgG Ydjg ZGdHG hbjd efgG HeYfi GdGJHGY dCf GdeUdj LeGYI JGHY dGeGeg hgh JGHY GdfHj Udi Gddg Ydjg hSde hbjd ef Udi HeYfi MQc (B...s
(3BNQgG (B:s
.. (3bhdg hbO JbOQ GdcdGe aj GdChdjf hEfeG CYGOg GdeUfa gfG djchf GSJKfGA Yf GdCFeI GdPjf LYdge Chdi ef ZjQge HeYfi Cf gDdGA Chdi Ef de jchfhG HCMO gPg GdUaGJ aEf cQGgI EeGeJge YGeI (B...(3Je cJGH GdUdGIs
(3Yf fSNI GdeUfas
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3\232s
(3gOjI GdYGQajf (B1\318s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis